Effects on the sex hormone profile in obese patients undergoing bariatric surgery - Ana I. López; Ana Ma. Ortiz-Zableh; Andrés F. Quiñones-Roa; Natalia Patiño-Covelli; Paula Silva; Paul A. Camacho; Bernardo Santamaria-Fuerte (Urología Colombiana)
We aimed to carry out a systematic review and meta-analysis of the effects of bariatric surgery on fertility in men with obesity. To assess the methodological quality of the included studies, the Cochrane-ROBINS-I tool for non-randomized studies was used. Three hundred and eighty-four articles were found. A statistically significant improvement in total testosterone levels was evidenced in all the patients; some studies did not find a correlation between this increase and the improvement in seminal parameters. Only one article showed a slight increase in estradiol levels (not statistically significant, 33.3-32 pg/mL, p: 0.68). Normal or low levels of LH and FSH were present both before and after the procedure. The total sperm count decreased at 6 months and was significantly lower at 12 months. There was not evidence of changes in seminal volume, sperm motility, and vitality. Although our systematic review shows changes on sexual hormonal parameters in men, with an increase in total testosterone levels, a negative one was also found on semen quality. More prospective and randomized studies are required, hopefully of the Latin American population, which can help confirm this association.